P38 Assessment of neurodevelopment and school performance of late and moderate preterms at 11–12 years of age. (6th June 2017) - Kucur, Ozge; Kavuncuoglu, Sultan; Tarakcioglu, Mahmut Cem; Payasli, Muge; Aldemir, Esin
Abstract : Aims: Evaluate somatic growth and neurodevelopmental outcome of late and moderate preterms at 11–12 years of age, research the effect of perinatal, neonatal, socioeconomic and cultural risk factors. Methods: Modarate and late preterms monitored in Bakirkoy Obstetrics and Paediatrics Training and Research Hospital between the dates January and December 2004 were included in this study. Mother's age, chronic diseases, premature rupture of membrans, placenta patologies, Apgar score were examined as perinatal risk factors. Duration of admission in intensive care unit, respiratory problems, intracranial haemorrhage, periventricular leukomalacia, sepsis, necrotizing enterocolitis, retinopathy of prematurity were assessed as neonatal morbidities. Full physical and detailed neurologic examination was performed on every patient. PEDS test, which examines families' concerns about their children and PSC test examining behaviour problems were also performed. Wisc-r test was used to calculate verbal, performance and full scale intelligence quotient, Report grades were used to evaluate school performance, socioeconomic level was determined through a poll. Results: We examined 41 children (18 girls, 23 boys), mean age was 11, 6 years. 5 cases (12, 2%) were below tenth height percentile, 10 (24, 4%) were below tenth weight percentile. Perinatal risk factors were not associated with verbal or numerical intelligence. As for neonatal morbidites; sepsis was associated with verbal intelligence, periventricular leukomalacia had a negative impact on verbal, performance and full scale intelligence. Socioeconomic level showed medium positive correlation with numerical and full scale intelligence. Children with concerned parents had significantly lower verbal, performance and full scale intelligence quotient, cases with a positive PSC score had a similar outcome. Girls had a better school performance, nevertheless there was no significant difference in intelligence quotient between two genders. As major neurologic deficits, three cases had mental retardation (Wisc-r score<70), one case was blind in one eye. Cases with major neurologic deficit had a lower full scale intelligence quotient and school performance. Conclusions: Modarate and late preterms have a higher risk than terms in terms of somatic growth and neurodevelopment. Consequently, long term follow-up of moderate and late preterms, like early preterms, is crucial for early diagnosis, treatment and rehabilitation